Muslims in Putin's Russia - Merati, Simona E. author. aut Link
XI, 241 p.
Keywords: This book offers a novel interpretation of Russian contemporary discourse on Islam and its influence on Russian state policies. It shifts the analytical perspective from the discussion about Russia's Islam as a potential security threat to a more comprehensive view of the relationships of Muslims with Russia as a state and a civilization. The work demonstrates how many Muslims increasingly express a sense of belonging to Russia and are increasingly willing to contribute to state building processes.